2010
DOI: 10.1097/shk.0b013e3181e14f1d
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Asphyxia Induces the Nitration of Cardiac Myosin Light Chain 2 That is Associated with Cardiac Systolic Dysfunction

Abstract: Background Hypoxia followed by reoxygenation (H-R) observed during perinatal asphyxia is a serious complication with a high mortality and morbidity rate which may cause adverse cardiovascular effects in neonates. Our aim was to determine if oxidative stress related to H-R induces peroxynitrite-dependent modifications of the cardiac contractile protein, myosin regulatory light chain 2 (MLC2) and whether this is associated with development of cardiac systolic dysfunction. Methods and Results Twelve newborn pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 35 publications
2
40
0
Order By: Relevance
“…This is not a 493 surprising result when the myosin is a major structural protein of the muscle sarcomere 494 in association with actin and other contractile proteins. The MYL3, MYL6B and MYL2 495 proteins play important structural and functional roles by supporting the structure of the 496 22 myosin neck region and fine-tuning the kinetics of the actin-myosin interaction [53]. 497 We also found that levels of MYL3, MYL6B and MYL2 were lower in DFD than in 498 normal meat, probably because of a more intensive enzymatic degradation of myofibril 499 structure, which can contribute to explain its tenderness differential.…”
Section: Tof/tof Ms (Supplementarymentioning
confidence: 61%
See 1 more Smart Citation
“…This is not a 493 surprising result when the myosin is a major structural protein of the muscle sarcomere 494 in association with actin and other contractile proteins. The MYL3, MYL6B and MYL2 495 proteins play important structural and functional roles by supporting the structure of the 496 22 myosin neck region and fine-tuning the kinetics of the actin-myosin interaction [53]. 497 We also found that levels of MYL3, MYL6B and MYL2 were lower in DFD than in 498 normal meat, probably because of a more intensive enzymatic degradation of myofibril 499 structure, which can contribute to explain its tenderness differential.…”
Section: Tof/tof Ms (Supplementarymentioning
confidence: 61%
“…It is well-recognized that MYL2 is highly 522 phosphorylated and that this phosphorylation is crucial for the regulation of MYL2 [56]. 523 Levels of MYL2 phosphorylation around 30-40% have been reported in humans and pig 524 [53]. Interestingly, the N-terminal domain in the human orthologue MYL2 contains a 525…”
Section: Tof/tof Ms (Supplementarymentioning
confidence: 99%
“…Both the MLC1 and MLC2 isoforms are subject to tyrosine nitration and cysteine S-nitrosylation in cardiac models of oxidative stress: MLC1 is S-nitrosylated at . These changes promoted degradation of both isoforms by MMP-2 (Doroszko et al 2009(Doroszko et al , 2010Polewicz et al 2011). It has been consistently demonstrated that inhibition of MMP-2 and nitration/nitrosylation of MLC1 attenuates ischemia/ reperfusion injury and prevents MLC1 degradation in isolated rat hearts.…”
Section: Impact Of Oxidative Stress On Cardiomyocyte Stiffness Sarcommentioning
confidence: 99%
“…Increased peroxynitrite production also induces MLC1 nitration/nitrosylation, leading to its increased degradation by the proteolytic enzyme MMP-2. This in turn suppresses cardiomyocyte contractility during either reoxygenation or reperfusion (Doroszko et al 2010;Polewicz et al 2011). Both the MLC1 and MLC2 isoforms are subject to tyrosine nitration and cysteine S-nitrosylation in cardiac models of oxidative stress: MLC1 is S-nitrosylated at .…”
Section: Impact Of Oxidative Stress On Cardiomyocyte Stiffness Sarcommentioning
confidence: 99%
“…But under hypoxic conditions, MLC2 is assaulted by reactive oxygen species (ROS), especially in the presence of nitric oxide (NO), by the aggressive fusion product peroxynitrite. This results in MLC2 degradation and subsequent systolic dysfunction (9). However, previous research has indicated that propofol might interfere with this cascade (10).…”
mentioning
confidence: 95%